Campur Kode dalam Web Series My Nerd Girl Season 3 serta Implikasinya terhadap Pembelajaran Bahasa Indonesia Siswa Kelas XII SMA - Monaratue Hutasoit; Patrisia Cuesdeyeni; Yuliati Eka Asi; Misnawati Misnawati (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
The purpose of this study is (1) to describe the form of code mixing in the web series My Nerd Girl Season 3. (2) describe the factors that affect the occurrence of code mixing in the web series My Nerd Girl Season 3. (3) To describe the implications of the results of the mixed code research in the web series My Nerd Girl Season 3 on the Indonesian learning of grade XII high school students. This research is a qualitative descriptive research that aims to explain and explain the problems studied in the form of the phenomenon of code mixing. The source of this research data is the web series My Nerd Girl Season 3. The data in this study are the results of recording in the form of sentences and paragraphs related to the object of research, namely mixing code in the My Nerd Girl Season 3 Web Series, as well as images obtained from screenshots of the My Nerd Girl Season 3 Web Series which show the seconds and minutes of the code mixing phenomenon. The results of the research from the analysis of code mix in the My Nerd Girl Season 3 web series are as follows. There are as many as 64 data consisting of mixed forms of word form codes, phrases, idioms, basters, word repetition, and clauses. As well as 64 data also regarding the factors that affect the code mixing that occurs, these factors are divided into role identification factors, variety identification factors and desire factors to explain. The results of the study are implicated in the Indonesian Module of the Independent curriculum for grade XII students of high school in even semester in chapter 6. Writing good practices and stories about the environment, subchapters. G. identify the character, plot, and language of the novel. The material discussed was in the form of analyzing the language of the dialogue of the characters in the novel.